Breeding varieties and seed production chain of minor cereals in India: Status and strategies - CHAUHAN, J S; SINGH, K H; CHOUDHURY, P R; SINGH, B B; KUMAR, VISHNU (The Indian Journal of Agricultural Sciences, 2023)
Minor cereals such as barley and small millets contributed 1.13–1.73 and 1.95–2.78% to the total cereals production and acreage, respectively, during 2010–11 to 2020–21. The present study analyses the trends in area, production and yield (2010–11 to 2020–21); breeding varieties and seed production chain of minor cereals during 2010–11 to 2021–22. Barley acreage ranged between 7.0 lakh ha (2010–11, 2012–13) to 5.9 lakh ha (2019–20), registering a decline of 18.6%. Production showed an increase from 3.8% (2011–12) to 17.3% (2013–14) during this period except for 2015–16, when production declined by 7.9% over 2010–11. The changes in acreage, production and seed yield of finger millet during 2020–21 over 2010–11 were -11.0%, +3.6% and +1.1%, respectively. Other small millets (kodo millet, barnyard millet, foxtail millet, proso millet and little millet) showed declining pattern since 2010–11 in acreage from 8.0 lakh ha to 4.4 lakh ha during 2020–21, a reduction of about 45.0% and consequently decline in production by 21.5%. Nevertheless, seed yield/ha increased by 41.2% and reached 781 kg (2020–21) from 553 kg (2010–11). Of the 135 high yielding and climate resilient varieties developed during 2011–23, 107 were released and notified during 2016–22 and only 39 were inducted in to the seed production chain until 2021–22. Breeder and foundation seed production was always higher than the indent/demand during the period under analysis. Seed requirement of barley and small millets has also been worked out considering seed multiplication ratio, seed replacement rate (SRR) and highest acreage and suggested action plan to enhance production of these crops through seed/variety replacement.